2015
DOI: 10.1038/srep16107
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effects of incarvillateine, a monoterpene alkaloid from Incarvillea sinensis and possible involvement of the adenosine system

Abstract: Incarvillea sinensis is a Bignoniaceae plant used to treat rheumatism and relieve pain in traditional Chinese medicine. As a major component of I. sinensis, incarvillateine has shown analgesic activity in mice formalin tests. Using a series of animal models, this study further evaluated the effects of incarvillateine against acute, inflammatory, and neuropathic pain. Incarvillateine (10 or 20 mg/kg, i.p.) dose-dependently attenuated acetic acid-induced writhing, but did not affect thermal threshold in the hot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 48 publications
3
42
1
Order By: Relevance
“…However, recent evidence suggests that DMPX also blocks A 2B (Wang et al, 2015). Therefore, it is possible that PDRN could effectively work through other adenosine receptors, including A 2B .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence suggests that DMPX also blocks A 2B (Wang et al, 2015). Therefore, it is possible that PDRN could effectively work through other adenosine receptors, including A 2B .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the receptors of these systems, present in peripheral and central sensory afferents fibers, have an important role in visceral pain maintenance (Wang et al, ; Yin et al, ). Our results indicated the antinociceptive action of STLE on writhing response was partially prevented by interacting through opioid receptor‐mediated and A1 adenosine receptor, suggesting a concomitant involvement of opioid and adenosine receptor systems in STLE antinociceptive effect from acetic acid test.…”
Section: Resultsmentioning
confidence: 99%
“…Uliginosin B is a naturally occurring acylphloroglucinol that reduces pain, and its MoA appears to involve adenosine signaling [94]. Incarvillateine is a complex monoterpene alkaloid that induces an antinociceptive effect, which is associated with AR signaling (using 26 and 29 at 0.1 and 1 mg/kg, i.p., respectively), but not opioid receptor activation [95]. Thus, various traditional medicines may in fact work through an adenosinergic MoA.…”
Section: Pain Antidepressant Sleep and Other Behavioral Interventionmentioning
confidence: 97%